Adherence to antiretrovirals in people coinfected with the human immunodeficiency virus and tuberculosis - Larissa de Araújo Lemos; Maria Luciana Teles Fiuza; Renata Karina Reis; André Carvalho Ferrer; Elucir Gir; Marli Teresinha Gimeniz Galvão (Universidade de São Paulo, 2016)
Objective: assess the adherence levels to antiretroviral therapy in people coinfected with HIV/tuberculosis and correlate these levels with the sociodemographic and clinical variables of the study population. Method: cross-sectional study involving 74 male and female adults coinfected with HIV/tuberculosis. For the data collection, a sociodemographic and clinical assessment form and the Antiretroviral Treatment Adherence Assessment Questionnaire were used. For the data analysis, the software STATA version 11 was used, through descriptive statistics, Fisher's chi-square exact test and the probability test. Results: men were predominant (79.7%), between 30 and 39 years of age (35.1%), low income (75.7%) and pulmonary tuberculosis (71.6%). Adherence to antiretroviral therapy was inappropriate in 78.1% of the men; 61.0% of single people; 47.0% unemployed and 76.5% among people gaining less than one minimum wage. A significant difference was observed between compliance and length of use of antiretrovirals (p=0.018), sexual orientation (p=0.024) and number of children (p=0.029). Conclusion: the coinfected patients presented inappropriate adherence to the antiretrovirals, a fact that negatively affects the health conditions of the people living with HIV/tuberculosis coinfection. A statistically significant correlation was found between the levels of adherence and some sociodemographic and clinical characteristics.